2018
DOI: 10.1186/s12960-018-0304-x
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about community-based health worker programs? A systematic review of existing reviews on community health workers

Abstract: ObjectiveTo synthesize current understanding of how community-based health worker (CHW) programs can best be designed and operated in health systems.MethodsWe searched 11 databases for review articles published between 1 January 2005 and 15 June 2017. Review articles on CHWs, defined as non-professional paid or volunteer health workers based in communities, with less than 2 years of training, were included. We assessed the methodological quality of the reviews according to AMSTAR criteria, and we report our fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
439
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(520 citation statements)
references
References 124 publications
20
439
0
12
Order By: Relevance
“…Evidence of effects on retention is mixed—short‐range evaluation of the Zambian Health Worker Retention Scheme showed positive effects, but a longer‐range piece across workforce cadres did not support these findings Skills mix (task shifting) approaches have been successfully used to address shortages of more highly skilled but scarcer professional groups supporting particular areas of service delivery . Nonformal cadres of health workers such as community health workers can help address staff shortages, as long as the tasks are not too complex …”
Section: State Of the Evidencementioning
confidence: 99%
“…Evidence of effects on retention is mixed—short‐range evaluation of the Zambian Health Worker Retention Scheme showed positive effects, but a longer‐range piece across workforce cadres did not support these findings Skills mix (task shifting) approaches have been successfully used to address shortages of more highly skilled but scarcer professional groups supporting particular areas of service delivery . Nonformal cadres of health workers such as community health workers can help address staff shortages, as long as the tasks are not too complex …”
Section: State Of the Evidencementioning
confidence: 99%
“…The progress is significant even though the baselines are already quite high and margins for progress are naturally limited. Research suggests that the capacities of community health workers tend to wane rather quickly [11,23,24] and that refresher training effectively enhances their performance [12,25,26]. The CBDs of the 2017 and 2018 campaigns thus seemed to have benefited from the cumulative contribution of each initial campaign training session, the supervision provided by the health teams during each round, and the regular refresher training preceding each round.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the personal characteristics of community health workers can be associated with their performance [8,11,15,27], suggesting that the CBDs to be trained should be carefully selected [11,28]. However, recent reviews reveal that results, particularly with regard to performance compared by type and sex, are not always consistent [12], and that "studies of workers with lower baseline performance showed greater improvements in prescribing medications…, vaccinating children,… and counseling…" [29]. As well, the more educated CBDs, who are traditionally more productive, are also less committed and more likely to drop out [8,11,15,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the world strives to achieve Universal Health Coverage and the Sustainable Development Goals, primary healthcare is foundational to meeting these goals 1,2 . Community healthcare systems serve critical roles within strong primary healthcare delivery [2][3][4] . The World Health Organization's recent guidelines 5 for best practices of community health workers (CHWs) offer important guidance to policy makers and program implementers about how to develop strong community health service delivery and support low-and middle-income countries along the path towards universal health coverage.…”
Section: Introductionmentioning
confidence: 99%